2007
DOI: 10.1016/j.jeconom.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Income distribution and inequality measurement: The problem of extreme values

Abstract: International audienceWe examine the statistical performance of inequality indices in the presence of extreme values in the data and show that these indices are very sensitive to the properties of the income distribution. Estimation and inference can be dramatically affected, especially when the tail of the income distribution is heavy, even when standard bootstrap methods are employed. However, use of appropriate semiparametric methods for modelling the upper tail can greatly improve the performance of even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(211 citation statements)
references
References 20 publications
10
194
1
6
Order By: Relevance
“…12 This data set was previously used by Alfons et al (2013) in the context of robust estimation of the Gini index of inequality from survey data. The reason for robust estimation arises in this context because survey samples may contain extreme observations, which have large influence on estimates on many of the standard inequality measures (Cowell and Flachaire 2007). In the presence of extreme outliers, both estimation and inference for inequality indices can be unreliable.…”
Section: Monte Carlo Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 This data set was previously used by Alfons et al (2013) in the context of robust estimation of the Gini index of inequality from survey data. The reason for robust estimation arises in this context because survey samples may contain extreme observations, which have large influence on estimates on many of the standard inequality measures (Cowell and Flachaire 2007). In the presence of extreme outliers, both estimation and inference for inequality indices can be unreliable.…”
Section: Monte Carlo Resultsmentioning
confidence: 99%
“…The latter is a sum of a nonparametric inequality measure estimated for the non-rich and a parametric inequality index for the rich (see, e.g. Cowell and Flachaire 2007). 15 The Gini index of the Pareto model with the tail index α is: G = 1/(2α − 1).…”
Section: Monte Carlo Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three measures differ in their sensitivity towards changes in the mean or changes in the tails (see e.g. Bendel et al, 1989;Cowell and Flachaire, 2007). The coefficient of variation and the Gini coefficient are more sensitive to shifts in the mean compared to the variance of logs.…”
Section: Comparing the Distributions Of (Suitable) Applicantsmentioning
confidence: 99%
“…We have assumed that this level of data would be sought only when developing intra-country interventions using specific data for the country concerned. The inclusion of gender, however, in future research on the development of multidimensional health indicators is suggested Lastly, previous literature (Cowell and Flachaire, 2007) has suggested that inequality measures are in general sensitive to extreme values (due to war, famine and natural catastrophes) or "data contamination". Thus data quality would affect the analysis in our present study as outlying or erroneous subnational IMR's may thus have affected the calculated Theil measures.…”
Section: Developedmentioning
confidence: 99%